PENGARUH PENGGUNAAN MEDIA PEMBELAJARAN KAHOOT TERHADAP PENINGKATAN MOTIVASI DAN HASIL BELAJAR SISWA DISEKOLAH DASAR - Muhajir; Rusdi; Annisa Rahmadani; Hasmalia; Indrawati (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
One educational tool that can increase students' interest and motivation to learn is Kahoot. Research using the Kahoot app was also conducted in the only dasar school in one of the two provinces in Maros, UPTD Dasar Negeri 130 Inpres Gantarang Tompobulu, for fourth-grade students studying pancasila. The purpose of this study is to examine the effects of using Kahoot as an educational medium on student learning outcomes. The sample population used in this study is made up of students in grades IV, whereas the sample size that was selected is a subset of approximately fifteen students. The type of analysis used in this study is experimentation analysis using the method of experimentation.One Posttest and Pretest Group. The data collection technique used is called a test. According to the study, there are differences in the learning outcomes before and after the experiment.